Enhancing Learning Outcomes in Basic Electricity and Electronics: The Power of Simulation Media in Problem-Based Learning - Mustaqim, Bima; Opetu, Demitila Okola; Sibuea, Abdul Muin; Siagian, Sahat; Junaidi, Agus (Vocational: Journal of Educational Technology, 2025)
This study investigates the impact of simulation media in problem-based learning on student learning outcomes in Basic Electricity and Electronics. The research problem addresses the low student engagement and learning performance due to conventional teaching methods. The purpose of this study is to compare the effectiveness of Livewire and Proteus simulation media in enhancing students' understanding of direct current circuit analysis. This research employs a quasi-experimental method with a Two-Group Pretest-Posttest Design. The study sample consists of 64 tenth-grade students from the Electrical Power Installation Engineering program at SMK Negeri 1 Percut Sei Tuan, divided into two groups: one using Livewire simulation and the other using Proteus simulation in problem-based learning. Data was collected through pretests and posttests, analyzed using t-tests to determine differences in learning improvement. The results reveal that students using Livewire simulation media achieved significantly higher post-test scores (average 80.3) compared to those using Proteus simulation media (average 63.7). These findings suggest that Livewire is more effective in facilitating conceptual understanding and problem-solving skills. The implications highlight the need for integrating technology-based learning tools to enhance vocational education outcomes. Schools and educators should consider incorporating simulation-based learning strategies to improve student engagement and academic performance.